2011
DOI: 10.1007/s11596-011-0580-3
|View full text |Cite
|
Sign up to set email alerts
|

Antilithic effects of extracts from Urtica dentata hand on calcium oxalate urinary stones in rats

Abstract: This study examined the potential antilithic effects of a traditional Chinese medicine Urtica dentata Hand (UDH) in experimental rats and screened the optimal extract of UDH as a possible therapeutic agent for kidney stones. The rat model of urinary calcium oxalate stones was induced by intragastric (i.g.) administration of 2 mL of 1.25% ethylene glycol (EG) and 1% ammonium chloride (AC) for 28 days and was confirmed by Color Doppler ultrasound imaging. The rats in different experimental groups were then intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Indeed, its aerial part (methanol extract) also exerts antiurolithiatic potential can suppress the increased levels of urinary calcium and creatinine while significantly reducing the renal deposition of calcium and oxalate. U. dentata (n-butanol extract) also exert antiurolithiatic activity, prevent the deposition of calcium oxalate, and protect renal tissue from injury produced by kidney calculi (rat model) ( Table 13 ) [ 112 , 124 ].…”
Section: Pharmacological Activities Of the Genus Urticamentioning
confidence: 99%
“…Indeed, its aerial part (methanol extract) also exerts antiurolithiatic potential can suppress the increased levels of urinary calcium and creatinine while significantly reducing the renal deposition of calcium and oxalate. U. dentata (n-butanol extract) also exert antiurolithiatic activity, prevent the deposition of calcium oxalate, and protect renal tissue from injury produced by kidney calculi (rat model) ( Table 13 ) [ 112 , 124 ].…”
Section: Pharmacological Activities Of the Genus Urticamentioning
confidence: 99%
“…Nowadays, the effective treatment for nephrolithiasis is a minimally invasive treatment, including ureteroscopic laser lithotripsy and shock wave lithotripsy . To improve the success of surgery and relieve postoperative symptoms, lithotripsy is usually combined with drug treatments. Potassium citrate is often recommended as the therapeutic drug, , whereas many traditional Chinese medicine (TCM) are clinically used as drugs for kidney stones in old ancient China. , …”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al. 21 found that an N-butanol extract of Urtica dentata hand prevented CaOx deposition and protected renal tissue in a rat nephrolithiasis model. These effects possibly resulted from a combination of the anti-inflammatory and analgesic effects of the extract in combination with its urination-promoting action.…”
Section: Discussionmentioning
confidence: 99%